A Developed Graphical User Interface for Power System Stability and Robustness Studies - Ghouraf Djamel Eddine; Naceri Abdellatif; Abid Mohamed; Kabi Wahiba (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper present the realization and development of a graphical user interface (GUI) to studied the stability and robustness of power systems (analysis and synthesis), using Conventional Power System Stabilizers (CPSS - realized on PID scheme) or advanced controllers (based on adaptive and robust control), and applied on automatic excitation control of powerful synchronous generators, to improve dynamic performances and robustness. The GUI is a useful average to facilitate stability study of power system with the analysis and synthesis of regulators, and resolution of the compromise: results precision / calculation speed. The obtained Simulation results exploiting our developed GUI realized under MATLAB shown considerable improvements in static and dynamic performances, a great stability and enhancing the robustness of power system, with best precision and minimum operating time. This study was performed for different types of powerful synchronous generators.